Website Design and Development to Help Create and Develop a Business to Increase the Number of MSMEs - Yogi Prasetyo; Btari Mariska Purwaamijaya; Syti Sarah Maesaroh (Jurnal Mantik, 2022)
The Covid-19 pandemic is now having quite serious consequences for the sustainability of the economy in Indonesia, this is because the government has established a policy of limiting community social activities where this policy is used to reduce the spread of Covid-19. As a result of this policy, economic activity barely runs at all. Because of this, the total number of MSMEs in Indonesia inevitably experienced a drastic decline and increased the number of unemployed. requires a treatment that is in line with current technological developments. One strategy to increase the number of MSMEs and reduce unemployment can be done by developing a website-based application that will be named "warung kita" where this website application is specifically to help people start their businesses, starting from providing goods at supplier prices that can be resold, market information regarding the goods to be sold, to education about strategies for selling. The development of this website-based application will be developed using the framework so that security in this website application is guaranteed.